Agrovoltaic system implementation for optimizing land productivity and sustainability under solar panel area in West Sumbawa - Komarudin, Nurul Amri; Sari, Ratna Nurmalita; Nairfana, Ihlana; Tubal, Jairus Jesse M.; Sadidan, Ikhwanussafa (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Greenhouse gas emissions are projected to increase by 50% by 2050, primarily due to reliance on non-environmentally friendly energy sources. The transition toward clean and renewable energy is therefore widely regarded as a key strategy for mitigating this trend.  West Nusa Tenggara possesses substantial potential for renewable energy development, particularly through solar power plants, owing to its abundant sunlight. In West Sumbawa, PT Medco Energi, via its subsidiary PT MPSoS, has implemented solar technology by installing panels on a 27-hectare site, capable of generating 26.8 MWp of energy. To further optimize land-use efficiency, PT MPSoS introduced an agrovoltaic approach that integrates solar energy generation with agricultural activities on the same land area. In collaboration with academic partners, PT MPSoS cultivated seedless watermelons beneath the solar panel structures. This study aimed to assess the feasibility and effectiveness of agrovoltaic systems in enhancing land-use efficiency through the integration of solar energy production and agricultural activity. A field experiment was conducted in which  seedless watermelons were grown beneath solar panels across 11 panel arrays, comprising three small plots (21 m x 6 m each) and eight large plots (31 m x 6 m each). Overall crop performance was assessed qualitatively based on plant growth success. Preliminary results indicate a crop establishment success rate exceeding 80%, underscoring the potential of agrovoltaic systems to contribute simultaneously to energy generation and food sustainability.